Is Metabolic Syndrome Useful for Identifying Youths with Obesity at Risk for NAFLD? - Procolo Di Bonito; Anna Di Sessa; Maria Rosaria Licenziati; Domenico Corica; Malgorzata Wasniewska; Giuseppina Rosaria Umano; Anita Morandi; Claudio Maffeis; Maria Felicia Faienza; Enza Mozzillo; Valeria Calcaterra; Francesca Franco; et al. (MDPI AG, 2023)
The definition of metabolic syndrome (MetS) in childhood is controversial. Recently, a modified version of the International Diabetes Federation (IDF) definition was proposed using reference data from an international population for high waist circumference (WC) and blood pressure (BP), while the fixed cutoffs for lipids and glucose were not changed. We analyzed MetS prevalence using this modified definition (MetS-IDFm) and its association with non-alcoholic fatty liver disease (NAFLD) in 1057 youths (age 6-17 years) with overweight/obesity (OW/OB). A comparison with another modified definition of MetS according to the Adult Treatment Panel III (MetS-ATPIIIm) was performed. The prevalence of MetS-IDFm was 27.8% and 28.9% by MetS-ATPIIIm. The Odds (95% Confidence Intervals) of NAFLD was 2.70 (1.30-5.60) (p = 0.008) for high WC, 1.68 (1.25-2.26)(p = 0.001) for MetS, 1.54 (1.12-2.11)(p = 0.007) for low HDL-Cholesterol, 1.49 (1.04-2.13)(p = 0.032) for high triglycerides and 1.37 (1.03-1.82)(p = 0.033) for high BP. No substantial difference was found in the prevalence of MetS-IDFm and frequency of NAFLD compared to Mets-ATPIIIm definition. Our data demonstrate that one third of youths with OW/OB have MetS, whichever was the criterion. Neither definition was superior to some of their components in identifying youths with OW/OB at risk for NAFLD.